Project-Based Learning On Solar System Materials In Grade 6 Elementary School - Muhammad Andi Tanri Prasetyo; Anggun Purnomo Arbi (PT. Gudang Pustaka Cendekia, 2024)
This study aims to explore the impact of Project-Based Learning (PBL) implementation on grade 6 students' understanding of solar system material at SDN Kedungsugo 1 Prambon. The research method used a descriptive qualitative approach involving grade 6 students and science teachers. The results showed that PBL was effective in increasing students' involvement and understanding of the solar system concept. The implication is that PBL can be used as a dynamic and useful teaching method in improving students' learning experience in elementary schools. Suggestions for improvement involve diversification of teaching materials, further training for teachers, and measurement of long-term impact on students' concept understanding.